"When that wounds are evil healed”: Revisiting pleonastic that in early English medical writing - Calle Martín, Javier (Adam Mickiewicz University, 2017)
The origin of pleonastic that can be traced back to Old English, where it could appear in syntactic constructions consisting of a preposition + a demonstrative pronoun (i.e., for þy þat, for þæm þe) or a subordinator (i.e., oþ þat). The diffusion of this pleonastic form is an Early Middle English development as a result of the standardization of that as the general subordinator in the period, which motivated its use as a pleonastic word in combination with many kinds of conjunctions (i.e., now that, if that, when that, etc.) and prepositions (i.e., before that, save that, in that) (Fischer 1992: 295). The phenomenon increased considerably in Late Middle English, declining rapidly in the 17th century to such an extent that it became virtually obliterated towards the end of that same century (Rissanen 1999: 303–304). The list of subordinating elements includes relativizers (i.e., this that), adverbial relatives (i.e., there that), and a number of subordinators (i.e., after, as, because, before, beside, for, if, since, sith, though, until, when, while, etc.). The present paper examines the status of pleonastic that in the history of English pursuing the following objectives: (a) to analyse its use and distribution in a corpus of early English medical writing (in the period 1375–1700); (b) to classify the construction in terms of genre, i.e., treatises and recipes; and (c) to assess its decline with the different conjunctive words. The data used as source of evidence come from The Corpus of Early English Medical Writing, i.e., Middle English Medical Texts (MEMT for the period 1375–1500) and Early Modern English Medical Texts (EMEMT for the period 1500–1700). The use of pleonastic that in medical writing allows us to reconsider the history of the construction in English, becoming in itself a Late Middle English phenomenon with its progressive decline throughout the 16th and 17th centuries.
Keywords: Early Modern English; historical syntax; medical writing; Middle English; pleonastic that